2014
DOI: 10.4186/ej.2014.18.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Approach to Arowana Gender Identification Problem using Algorithm of Inventive Problem Solving (ARIZ)

Abstract: This paper presents a systematic approach to arowana gender identification problem using algorithm of inventive problem solving (ARIZ). Arowana is a beautiful and expensive fish. Many farms try to improve their efficiency in breeding arowana, but the problem is that arowana is monomorphic, which makes it difficult to distinguish male from female just from their appearance. This causes difficulties in mating and selling of arowana. Many trial-and-error methods have been used with little success. The problem of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…On the other hand, the widely used standard methods based on DNA sequencing, i.e., polymerase chain reaction (PCR) and gel electrophoresis are labour-, time-, and resource-demanding. An alternative algorithm of inventive problem solving (ARIZ) method was previously employed for the detection of arowana gender detection [ 18 ]. ARIZ is an alternative tool for gender detection, containing nine different parts and a total of 40 complex steps.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the widely used standard methods based on DNA sequencing, i.e., polymerase chain reaction (PCR) and gel electrophoresis are labour-, time-, and resource-demanding. An alternative algorithm of inventive problem solving (ARIZ) method was previously employed for the detection of arowana gender detection [ 18 ]. ARIZ is an alternative tool for gender detection, containing nine different parts and a total of 40 complex steps.…”
Section: Introductionmentioning
confidence: 99%
“…When the system is classified into subsystems, it will be easier to be managed. [13,14]. It clearly shows the inside relation among the actors, the constraints, and the data.…”
Section: Systems Thinking Framework Designmentioning
confidence: 91%
“…The study proposed an ARIZ-based DSS to integrate multiple dimensions of parameters into a single decision support tool. More ARIZbased integration studies can be found in on an eco-innovation biomimetic design tool and [5] on arowana gender identification among others.…”
Section: Analyzing the Solutionmentioning
confidence: 99%